Forelimb muscle activity during level and progressive incline and decline walking in dogs and implications for rehabilitation - Cain, Rachel Mariël; Stanford, Kate; Drum, Marti; Richards, Jim; Levine, David; Millis, Darryl; Ursini, Tena (Frontiers in Veterinary Science, 2025)
IntroductionShoulder pathologies are a common reason for presentation to veterinary sports medicine and rehabilitation practices. Currently there are no standardized rehabilitation protocols for shoulder injuries but controlled walking, either on flat ground or on inclines/declines, is recommended in nearly every recovery rehabilitation program. The objective of this study was to evaluate the peak and average muscle activity of commonly targeted forelimb muscle groups using fine-wire and surface electromyography (EMG) during treadmill walking at five treadmill positions. Our hypothesis was that the forelimb muscle activity would be significantly higher during decline walking than level walking and significantly lower during incline walking.MethodsFine-wire and surface EMG of the supraspinatus, deltoideus, biceps brachii and lateral head of the triceps brachii muscles were performed during treadmill walking at 0, 5% incline, 10% incline, 5% decline, and 10% decline. The average and peak muscle enveloped EMG signals for 10 gait cycles were compared between the treadmill positions.ResultsSignificant main effects were seen during decline walking for average supraspinatus muscle activity (p < 0.001), and both average and peak deltoideus muscle activity (p = 0.021, p < 0.001) respectively. There were no significant differences for peak or average lateral triceps brachii or biceps brachii activity between treadmill positions.ConclusionDecline walking significantly increases muscle activity in the supraspinatus and deltoideus muscles of dogs. This study provides new insights regarding the muscle activity of the thoracic limbs in dogs during various treadmill positions at the walk. The impact of incremental treadmill positions on the average supraspinatus EMG activity, along with increases in the average and peak EMG activity of the deltoideus muscle during decline walking should be considered when developing a therapeutic exercise plan in canine patients with shoulder injuries.